Fracture prevalence and its association with bone density among children living with HIV in Zimbabwe. (1st April 2023) - Rukuni, Ruramayi; Simms, Victoria; Rehman, Andrea M.; Mukwasi-Kahari, Cynthia; Mujuru, Hilda; Ferrand, Rashida A.; Gregson, Celia L.
Abstract : Objectives: HIV infection impairs bone density in children living with HIV (CLWH). We aimed to determine the prevalence of self-reported fracture (past or current), associated risk factors and disability, by HIV status in Zimbabwean children. Design: Cross-sectional study. Methods: We recruited CLWH aged 8–16 years taking antiretroviral therapy (ART) for ≥2 years from HIV clinics, and HIV-uninfected children from schools in Harare. Interviewer-administered questionnaires collected data on fracture site and management, sociodemographics, dietary calcium and vitamin D, physical activity and HIV history. Dual-energy X-ray absorptiometry (DXA) measured size-adjusted bone density. Results: We recruited 303 CLWH [mean (SD) age 12.5 (2.5) years; 50% female] and 306 children without HIV [12.5 (2.5) years; 51% female]. Median age at HIV diagnosis in CLWH was 3.0 years [interquartile range (IQR) 1.2, 5.9], and median ART duration 8.1 years [IQR 6.2, 9.5]. 53.8% CLWH had self-reported disability and/or functional impairment, vs. 29.4% children without HIV. Fracture prevalence was 5.9% with no difference by HIV status [21/306 (6.9%) vs. 14/303 (4.6%), P  = 0.24]. Male sex was associated with fractures. Low size-adjusted bone density ( Z -score < −2) was associated with prevalent fractures in CLWH {risk ratio [RR] 1.14 (95% confidence interval (CI) −0.02, 2.29]}, but not in children without HIV [RR −0.04 (−2.00, 1.91)], P -interaction = 0.27. All sought medical attention for their fracture(s), but CLWH were less often admitted to hospital [2/14 (14.3%) vs. 7/21 (33.3%)]. Conclusion: Prevalent fractures may be associated with low lumbar spine bone density in CLWH. Fracture surveillance and strategies to reduce future fracture risk are warranted as CLWH enter adulthood.